IMPLEMENTATION OF MANAGEMENT FUNCTIONS IN THE MANAGEMENT OF PROFESSIONAL ZAKAT AT THE NATIONAL AMIL ZAKAT AGENCY (BAZNAS) OF PADANGSIDIMPUAN CITY - Romando Yusrat; Arbanur Rasyid; Budi Gautama Siregar (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the implementation of management functions in the management of professional zakat at the National Zakat Agency (BAZNAS) of Padangsidimpuan City. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, with triangulation applied to ensure validity. The findings show that BAZNAS has implemented the four classical management functions—planning, organizing, implementing, and supervising—in managing professional zakat from civil servants. Planning is carried out through the preparation of zakat collection programs in cooperation with government institutions; organizing is realized through the formation of operational sub-units; implementation is conducted by collecting zakat through salary deductions and distributing it to mustahik via social and empowerment programs; while supervision is executed by an Internal Audit Unit to maintain accountability and transparency. Supporting factors include government affiliation and mayoral instructions, whereas inhibiting factors involve limited human resources, the absence of binding local regulations, restricted access to military and police institutions, and low awareness among civil servants. The study concludes that although BAZNAS has applied management principles in practice, improvements are still needed in human resource regeneration, regulatory frameworks, and digital zakat systems to optimize professional zakat management.